Measurements of indoor radon concentration levels in Kilis, Osmaniye and Antakya, Turkey during spring season - Can, Bayram; Canbazoglu, Cumhur; Albayrak, Nesli; Celebi, Nilgun; Dogru, Mahmut (Springer, 2012)
The fact that 50% of the natural radiation dose to which humans are exposed is caused by radon gas makes indoor radon measurements important. In this study, levels of indoor radon gas were measured in 204 houses in Kilis, Osmaniye and Antakya using passive nuclear track detectors. Cr-39 radon detectors were left in the living rooms of participants' houses, then analyzed at the Radon Laboratory of Health Physics Department in Cekmece Nuclear Research and Training Center (CANEM) of Atomic Energy Agency of Turkey (TAEK). Average indoor radon activity concentrations for Kilis, Osmaniye and Antakya were 50 Bq/m(3) (1.26 mSv/y), 51 Bq/m(3) (1.29 mSv/y) and 40 Bq/m(3) (1.01 mSv/y), respectively.
Keywords: Cr-39; Indoor radon; Effective dose; Chemical etching